PENGARUH KOMBINASI EKSTRAK JERUK BRASTAGI DAN WORTEL PER ORAL SEBELUM AKTIVITAS FISIK TERHADAP KADAR MALONDIALDEHID PLASMA MENCIT DALAM BERBAGAI DURASI AKTIVITAS FISIK - Felix Samuel; Hanna Goenawan; Aziiz Mardanarian Rosdianto; Juliati Juliati (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2018)
Under specific circumstances such as during aerobic predominant exercise, the production of free radicals increases and creates free radicals-endogen antioxidants imbalance. It causes oxidative stress. The level of oxidative stress can be recognized by measuring the level of plasma malondialdehyde (MDA). But the effect of physical activity and the effect of exogenous antioxidants supplementation is still not clearly known in the literature. Based on the background above, as a preliminary study, the writers conduct a study to investigate the plasma MDA level on mice which is given and not given a combination of Brastagi’s oranges and carrots juice before physical activity using mice’s treadmill for 10,20, and 30 minutes. The research method used in this study is an experimental laboratory study. As objects of this study are 24 mice(mus musculus), white-colored, male, weighting 25-30 grams, which is randomly chosen. The objects are divided into 2 groups, Group A: 12 mice (given a combination of Brastagi’s oranges and carrots juice before physical activity using mice’s treadmill) and group B: 12 mice (not given a combination of Brastagi’s orangesand carrots juice before physical activity using mice’s treadmill). Group A is divided into 3 subgroups: A1 (doing treadmill for 10 minutes), A2 (doing treadmill for 20 minutes), and A3 (doing treadmill for 30 minutes). The same procedure is employed for group B. Plasma MDA level measured after doing a physical activity using mice treadmill. The homogeneity of the result then was tested using Levene’s test and the normality of the result was tested using the Kolmogorov-Smirnov test (p>0.05). Further, the data were analyzed using an independent t-test (p≤0.05), one-way ANOVA (p≤0.05) then Duncan’s test were used. The analyzed data indicated a combination of Brastagi’s oranges and carrots juice supplementation given to mice before physical activity, for 10,20, and 30 minutes caused lower plasma MDA levels than mice not given a combination of Brastagi’s oranges and carrots juice before physical activity. The differences are 38,44% (0,5277 vs 0,8571) (A1-B1); 37,96% (0,5866 vs 0,9455) (A2-B2); dan77,79% (0,8438 vs 1,6161) (A3-B3).The conclusion of the study suggested that a combination of Brastagi’s oranges and carrots juice supplementation given to mice before physical activity for 10,20, and 30 minutes caused lower plasma MDA levels than mice not given a combination of Brastagi’s oranges and carrots juice before physical activity.